Statistical damage constitutive model of soft rock based on Improved Hoek-Brown strength criterion - Zhenhua Wang; Zecheng Wang; Xin Chen; Gang Wang; Dongwei Li (Scientific Reports)
Abstract It is significant to study the stability of surrounding rock in soft rock tunnels to ensure construction safety and improve efficiency. Through triaxial shear tests on soft rock at various confining pressures, we observed the failure characteristics transitioning from strain softening to strain hardening as confining pressure increases. An improved Hoek-Brown strength criterion has been proposed to characterize the critical confining pressure effect of soft rock, with tensile strength in the tensile zone aligning with experimental results, showing an error of less than 5%. By assuming that the micro-unit strength of soft rock follows a two-parameter Weibull distribution, we constructed a statistical damage constitutive model for soft rock in mountain tunnels. This model provides a more realistic depiction of damage change, failure processes, and stress-strain evolution in soft rock, thereby validating its scientific and rational foundation. The research findings can serve as a valuable reference for mountain tunnel construction.